Radiative transfer model inversion for measuring maize leaf area index (directly related to crop productivity) - CGIAR Research Program on Maize (2021)
Results showed that the PROSAIL-based model provided the highest R2 value between ground and estimated LAI followed by the RF and SVM where R2 values were 0.65, 0.59 and 0.35 respectively.